Evidence-based practice in exercise science the six-step approach - Amonette, William E. 1977-; English, Kirk L. 1975-; Kraemer, William J. 1953- (Human Kinetics, 2016)
Exercise science practitioners have access to mountains of research findings, expert opinions, novel techniques, and program plans via blogs, fitness magazines, conference presentations, and peer-reviewed journals. To facilitate effective practice, practitioners must sift through this information and retain only the best evidence to form a sound base of knowledge. Evidence-Based Practice in Exercise Science: The Six-Step Approach equips readers with the basic skills and competencies for discerning the value of scientific research. Using a methodical approach, students and professionals will learn to identify appropriate evidence to support novel interventions and avoid counterproductive or dangerous information to eliminate ineffective exercise options. The authors, well-known advocates in the study and application of evidence-based practice in the field of exercise science, take the five-step method of evidence-based practice that has been established in medicine, adapt it specifically for exercise science, and expand it to embrace individuality in exercise training. The content is accessible for students in a variety of courses in exercise science curricula; those seeking certification through professional organizations; and practitioners in the fields of exercise, nutrition, sports medicine, and sport science. This text is an instruction manual in understanding and applying evidence-based practice. The process is divided into six steps that begin with asking a question and then finding, evaluating, implementing, confirming, and re-evaluating the evidence. Readers of Evidence-Based Practice in Exercise Science will explore these aspects: The philosophy of science and design of scientific studies; The use of search tools like PubMed and Google Scholar and how to rank or define the strength of the evidence; Practical suggestions for implementing evidence-based practice in the field to better advise and serve athletes, clients, and patients; Case studies that demonstrate realistic scenarios of how the evidence-based process may be used in a variety of sport and exercise settings. Each chapter opens with chapter objectives that provide a road map for learning, and a chapter conclusion summarizes main points and ensures understanding. The case studies cover topics including exercise prescription; exercise for special populations; nutrition and supplementation; and exercise devices, equipment, and apparel. Each case presents a realistic scenario that an exercise practitioner may experience, presents background information, formulates a question for investigation, describes a search of the literature, discusses the findings, and provides a recommendation for practice based on the best current evidence. Evidence-Based Practice in Exercise Science is grouped into four sections that assist readers in gaining a better understanding of the evidence-based practice paradigm, learning the step-by-step method, and acquiring experience in the evidence-based approach by working through practical examples using real-world scenarios. Part I offers foundational knowledge of evidence-based practice in exercise sciences. Part II introduces the six-step method of evidence-based practice with chapters that explore each step of the process in depth. Part III presents 16 case studies grouped into chapters by general topics. Part IV concludes the text with chapters on disseminating and sharing knowledge and the future of evidence-based practice in exercise science. By understanding the concepts and process of evidence-based practice, current and future sport, exercise, and health professionals will prescribe individualized programs and treatments that improve athletic performance and lead individuals toward better health. Embracing evidence-based practice will ultimately advance the field and produce optimal outcomes for clients, patients, and athletes.